Pretreatment apoptosis in carcinoma of the cervix correlates with changes in tumour oxygenation during radiotherapy - Sheridan, M T (Nature Publishing Group, 2000)
A relationship between hypoxia and apoptosis has been identified in vitro and in experimental tumours. The aim of this study was to investigate the relationship between apoptosis, hypoxia and the change in oxygenation during radiotherapy in human squamous cell carcinoma of the cervix. Forty-two patients with locally advanced disease underwent pretreatment evaluation of tumour oxygenation using an Eppendorf computerized microneedle electrode. Twenty-two of these patients also had a second evaluation of tumour oxygenation after receiving 40–45 Gy external beam radiotherapy. Paraffin-embedded histological sections were obtained from random pretreatment biopsies for all 42 patients. Apoptotic index (AI) was quantified by morphology on TUNEL stained sections. No correlation was found between pretreatment measures of AI and either the median pO(2)(r = 0.12, P = 0.44) or percentage of values < 5 mmHg (r = –0.02, P = 0.89). A significant positive correlation was found between AI and the change in tumour oxygenation (ratio of pre:post-treatment % values < 5 mmHg) following radiotherapy (r = 0.61, P = 0.002). The lack of correlation between apoptosis and hypoxia may occur because the Eppendorf measures both acute and chronic hypoxia, and the relative ability of acute hypoxia to induce apoptosis is unknown. These results indicate that cell death via apoptosis may be a mechanism of tumour reoxygenation during radiotherapy. © 2000 Cancer Research Campaign